Tacit Knowledge: Revisiting the epistemology of knowledge - Lejeune, Michel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
The concept of tacit knowledge encompasses all of the intricacy of the different experiences that people acquire over time, and which they utilize and bring to bear in carrying out tasks effectively, reacting to unforeseen circumstances, or innovating. The intuitive nature of tacit knowledge, its particular context, and the difficulty of expressing it in words call into question the very foundation of the notion of competency and its value in education. What parameters might be used to clarify tacit knowledge and its place within so-called “organizational” knowledge? Certain characteristics of tacit knowledge may contribute new considerations to the ongoing debate as to the true nature of competency.